Efektivitas dan Pertanggungjawaban Hukum Bill of Lading sebagai Dokumen Pengangkutan Perdagangan Internasional di Indonesia - Shelomita Liani Putri Zahra; Fakhira Aghnya Makaranu (Majelis: Jurnal Hukum Indonesia, 2025)
International trade involves cross-border buying and selling activities between countries, which in practice requires various transportation documents to ensure legal certainty and smooth operations. One of the main documents used is the Bill of Lading (Konosemen), which is a dated letter issued by the carrier as proof of receipt of goods to be transported to a certain destination and delivered to a specified recipient. The Bill of Lading has three essential functions: as a receipt of goods, as evidence of ownership, and as proof of a transportation contract. However, in practice, there are still frequent problems that hinder the optimal function of the Bill of Lading. One notable case is APL Co. Pte. Ltd. v. CV. Dua Sekawan Sejati, which involved discrepancies between the goods shipped and those stated in the Bill of Lading. This study adopts a normative juridical method by examining applicable legal provisions and theoretical concepts related to the law of contracts and transportation. The findings show that discrepancies between the goods shipped and those listed in the Bill of Lading constitute a breach of promise or default under Article 1320 of the Indonesian Civil Code. The Bill of Lading, in this case, serves as a legally binding transportation contract that obligates both parties to fulfill their respective responsibilities. Failure by one party to comply with the terms of the contract results in legal consequences in the form of claims for compensation by the aggrieved party. This research emphasizes the importance of accuracy and accountability in the issuance and use of Bills of Lading in international trade to avoid disputes and ensure legal certainty. Strengthening the regulation and enforcement of Bill of Lading functions is crucial for protecting the rights of parties engaged in cross-border trade.